Evaluation of the relationship between the occlusion parameters and symptoms of the temporomandibular joint disorder - Dzingutė, Agnė; Pileičikienė, Gaivilė; Baltrušaitytė, Aušra; Skirbutis, Gediminas (Acta medica Lituanica, 2017)
Background. The aetiology of temporomandibular joint disorders (TMD) is multifactorial, whereas occlusal disharmony is one of the predisposing factors. Researchers still discuss the relation between occlusion and TMD. Objective. The study aims to investigate the relation between static occlusal parameters and TMD clinical symptoms using T-Scan II analysis system. Material and methods. The sample consisted of 44 persons divided into the treatment group of 20 TMD patients and the control group of 24 subjects without TMD. The main task of T-Scan II computerized occlusal analysis system was to record every patient’s occlusion and estimate static occlusal parameters: centre of occlusal force, asymmetry index of maximum occlusal force and occlusion time. These results were compared between groups, data related to patients’ complaints and clinical symptoms. The analysis was carried out using Mann-Whitney U, Kruskal-Wallis and Chi-square tests. Results. Averages of the centre of occlusal force in TMD subjects were 6.55 ± 0.99 mm, in the control group – 5.88 ± 0.69 mm; the asymmetry index of maximum occlusal force averages: 15.90 ± 2.71 and 12.93 ± 1.88; occlusion time: 0.281 ± 0.036 s and 0.236 ± 0.022 s, respectively. There were no statistically significant differences between two groups but they were found in the centre of occlusal force and the asymmetry index in the two groups (p < 0.05). Conclusions. There exists a relation between complaints of patients with TMD and static occlusion parameters. Values of the centre of the occlusal force distance and the asymmetry index of occlusal force in TMD patients with pain in the temporomandibular joint (TMJ) were significantly higher than in the control group.